Analisis Dinamika Self Efficacy Dan Motivasi Kerja Terhadap Kinerja Guru Pendidikan Anak Usia Dini - Liza Anriyani; Hengki Yandri; Titin Kusayang (UIN Sultan Maulana Hasanudin Banten, 2024)
Teacher performance is always an interesting thing to discuss to see the level of achievement of results and the effectiveness of teachers in carrying out their duties, including their ability to teach (self efficacy), motivate students, manage classes, and internal and external encouragement, to make maximum contributions to the learning process and child development. This study aims to reveal the effect of self efficacy and work motivation on the performance of PAUD teachers. This study uses quantitative research using survey research design and questionnaires. The subjects of this study amounted to 60 people with the characteristics of PAUD teachers in Kerinci district. The research data were revealed using the Teacher Self efficacy Scale, Multidimensional Work Motivation Scale, PAUD Teacher Performance Scale, then the research data were processed using simple regression analysis and multiple regression. The results showed that self efficacy and work motivation have a significant influence on the performance of PAUD teachers. It is recommended that future researchers conduct a broader study, covering provincial or even national levels.